THE DIFFERENCE OF MUSCULOSKELETAL DISORDERS BEFORE AND AFTER WORKPLACE STRETCHING EXERCISE - Harahap, Mitha Aulia; Situngkir, Decy; Irfandi, Ahmad; Ayu, Ira Marti; Muda, Cut Alia Keumala (Journal of Vocational Health Studies, 2021)
Background: Workers who undertake occupations that require bending, climbing, crawling, reaching, twisting, excessive activity, or repeated movements may suffer from musculoskeletal disorders (MSDs). MSDs can be prevented by doing Workplace Stretching Exercise (WSE) which is useful for minimizing the risk of musculoskeletal injury, fatigue reduction, muscle balance, and posture improvement, and muscle coordination improvement. Purpose: To analyze the difference before and after giving WSE to the reduction of MSDs complaints. Method: This research takes a quantitative approach, utilizing a quasi-experimental design in one group before and after WSE administration. Total sampling is used for sampling. The respondents of this study were 34 workers in the production division of PT Crown Pratama in 2021. The T-paired test was utilized as a statistical test in this study. Result: The results of the univariate test mean MSDs complaints before and after WSE administration were 42.97 and 36.29. Conclusion: The bivariate test revealed differences in complaints of Musculoskeletal Disorders (MSDs) before and after workplace stretching exercise.